2019
DOI: 10.7717/peerj.7022
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, α-glucosidase inhibition and phytochemical profiling of Hyophorbe lagenicaulis leaf extracts

Abstract: Background Diabetes mellitus type II (DMT-2) is a widely spread metabolic disorder both in developed and developing countries. The role of oxidative stress is well established in DMT-2 pathogenesis. The synthetic drugs for DMT-2 are associated with serious side complications. Antioxidant and α-glucosidase inhibitory actions of phytochemicals from various plant species are considered as an alternative to synthetic drugs for DMT-2 management. The present study aimed to evaluate the antioxidant activity, α-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…A recent study reported the antioxidant behavior, α-glucosidase and α-amylase inhibitory action of Hyophorbe lagenicaulis leaf extracts. The phytochemical responsible for the antioxidant and enzyme inhibitory properties in leaf extract of Hyophorbe lagenicaulis were identified as kaempferol, rutin, hesperetin 5-O-glucoside, kaempferol-coumaroyl-glucoside, luteolin 3-glucoside, Isorhamnetin-3-O-rutinoside, trimethoxyflavone derivatives and citric acid 74 . Another investigation reported the strong antioxidant and α-glucosidase inhibitory potential of apigenin rich leaf extract of Cycas revoluta 75 .…”
Section: Uhplc-q-tof-ms/ms Analysis Uhplc-qtof-ms/ms Was Used For Mementioning
confidence: 99%
“…A recent study reported the antioxidant behavior, α-glucosidase and α-amylase inhibitory action of Hyophorbe lagenicaulis leaf extracts. The phytochemical responsible for the antioxidant and enzyme inhibitory properties in leaf extract of Hyophorbe lagenicaulis were identified as kaempferol, rutin, hesperetin 5-O-glucoside, kaempferol-coumaroyl-glucoside, luteolin 3-glucoside, Isorhamnetin-3-O-rutinoside, trimethoxyflavone derivatives and citric acid 74 . Another investigation reported the strong antioxidant and α-glucosidase inhibitory potential of apigenin rich leaf extract of Cycas revoluta 75 .…”
Section: Uhplc-q-tof-ms/ms Analysis Uhplc-qtof-ms/ms Was Used For Mementioning
confidence: 99%
“…The role of solvent polarity and extraction techniques is imperative for high extract yields. Extracts with high polyphenol concentrations reflect high antioxidant and related pharmacological activities [20,21]. Phenolics are vital plant bioactives with the ability to scavenge free radicals for improvement in physiological attributes especially under diseased or stressed conditions.…”
Section: Extract Yield Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…More than 90% of diabetic patients are suffering from diabetes mellitus type 2 (DMT2). Modern sedentary lifestyle, unhealthy food habits and obesity are key factors responsible for the development of DMT2 (William et al, 2019). These factors may also contribute to generate a state of oxidative stress by producing reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%